2003
DOI: 10.2527/2003.8171728x
|View full text |Cite
|
Sign up to set email alerts
|

Protein turnover and sensory traits of longissimus muscle from implanted and nonimplanted heifers1

Abstract: Primary bovine muscle cell culture studies were conducted to determine whether implanting heifers had a direct effect on in vitro protein synthesis and degradation and to determine the effect of implanting heifers on longissimus muscle palatability. Feedlot heifers (n = 96) were administered one of six implant regimens to characterize their effect on in vitro amino acid uptake and protein degradation. Treatments consisted of: 1) a nonimplanted control (NI/NI); 2) no implant on d 1 and Revalor-H administered on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 29 publications
1
9
0
2
Order By: Relevance
“…Platter et al (2003) found that implanted heifers maintained greater WBSF values through 21 d of aging. In agreement, Kerth et al (2003) and Boles et al (2009) also found that implanting heifers did not affect WBSF values at up to 21 d of aging.…”
Section: Growth-promoting Technologies Effectssupporting
confidence: 70%
“…Platter et al (2003) found that implanted heifers maintained greater WBSF values through 21 d of aging. In agreement, Kerth et al (2003) and Boles et al (2009) also found that implanting heifers did not affect WBSF values at up to 21 d of aging.…”
Section: Growth-promoting Technologies Effectssupporting
confidence: 70%
“…However, in the present study, steers received growth implants, as is the common practice in the industry [8]. Hormonal implants enhance amino acid uptake by muscle cells [15], increasing the number of satellite cells, rate of cell proliferation, and protein synthesis, and decreasing rate of protein degradation [16]. The net effect is a potential for increased N retention, provided cattle receive adequate metabolizable protein [17]- [20].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have reported no effect of testosterone and oestradiol on protein synthesis or degradation rates (Roeder et al 1986;Desler et al 1996), although others have shown an increase in protein synthesis alone (Martinez et al 1984;Hayden et al 1992). Kerth et al (2003) concluded that implantation of cattle with trenbolone acetate impacted both synthesis and degradation, with perhaps the strongest effect on protein synthesis.…”
Section: Effect Of Hgp Implants On Sensory and Objective Meat Qualitymentioning
confidence: 99%
“…There is mounting evidence that HGPs increase efficiency and growth rates of cattle by modifying protein turnover rates in the body (Kerth et al 2003;Dunshea et al 2005). In reviewing the interaction between protein turnover and eating quality, Koohmaraie et al (2002) proposed that if in part an increase in net protein in the live animal was achieved by a decrease in protein turnover (i.e.…”
Section: Introductionmentioning
confidence: 99%